Performance Motivation that affects performance of municipal employees in the area of Non Sang District Nong Bua Lam Phu Province - Rinsena, Bongkod; Sirimongkol, Thitaree (Journal for Developing the Social and Community, 2023)
The purposes of this research were to study the level of performance motivation of local officials in Non Sang district, Nong Bua Lam Phu province, to study the operational efficiency of local officials in Non Sang district, Nong Bua Lam Phu province and to study the influence of performance motivation affecting the operational efficiency of local officials in Non Sang district, Nong Bua Lam Phu province. This research was a quantitative research using the questionnaire as research tool. The sample group consisted of local officials in Non Sang district, Nong Bua Lam Phu province, with the total number of 262 people using convenience sampling method. The statistics used to analyze data comprised frequency, percentage, standard deviation and multiple regression analysis. The research results were found that performance motivation of local officials in Non Sang district, Nong Bua Lam Phu province, in overall, was rated at the high level, when considered in 4 aspects, it was found that it was rated at a high level in all aspects. Likewise, the operational efficiency of local officials in Non Sang district, Nong Bua Lam Phu province, in overall, was rated at the highest level, when analyzing opinions about the operational efficiency of local officials in Non Sang district, Nong Bua Lam Phu province in 4 aspects, it was found that, in overall, it was rated at a high level, when considered in each aspect, it was found that it was rated at a high level in all aspects. The performance motivation variables of local officials in Non Sang district, Nong Bua Lam Phu province had a positive relationship with the operational efficiency (y) with statistical significance at 0.05 level, including job achievement (X1), job characteristics (X3), recognition (X2) and advancement in position (X4) consisting of the coefficients at .547, .265, .044 and .041, respectively. These 4 variables could predict the operational efficiency (y) at 70.7% (adjusted R2 = .707).